Short-term forecasting with business surveys: Evidence for German IHK data at federal state level - Lars Wenzel; André Wolf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2013)
We investigate the performance of the IHK business climate indices as forecasting tools within a growth framework at the level of four federal states in Northern Germany. In doing this, we match quarterly index scores with estimates of quarterly production data, generated through a Chow-Lin procedure. Estimating the model reveals strong linkages of the index scores to short-term output growth at the regional level, even after controlling for prior information on the position in the business cycle as well as for nation-wide fluctuations. Examining the forecasting accuracy of our model by means of out-of-sample predictions confirms these results: the model clearly outperforms an autoregressive benchmark. This can to a large part be traced back to information conveyed by the IHK index.
Keywords: 330